SPLENIC VOLUME: CORRELATION BETWEEN COMPUTED TOMOGRAPHY AND ULTRASOUND MEASURMENTS (The Research of Medical Science Review, 2025)
Objective: To evaluate the correlation and agreement between splenic volume measurements obtained by computed tomography (CT) and ultrasonography (US) in adult patients without splenic pathology.Methodology: A prospective, cross-sectional study was conducted over 12 months at a tertiary care center. One hundred adult patients undergoing contrast-enhanced abdominal CT were enrolled. Within 72 hours, each patient underwent a standardized ultrasound examination. Splenic volume was estimated via the ellipsoid formula on US and by semi-automated segmentation using 3D post-processing software on CT. Statistical analysis included Pearson’s correlation, linear regression, Bland–Altman analysis, and intraclass correlation coefficient (ICC) to assess agreement and reproducibility.Results: The mean splenic volume was 231.5 ± 52.4 mL on CT and 219.8 ± 49.3 mL on US. The Pearson correlation coefficient between modalities was strong (r = 0.87, p < 0.001), with a regression model yielding R² = 0.76. Bland–Altman analysis revealed a mean bias of 11.7 mL with 95% limits of agreement from -27.4 to +50.8 mL. Inter-observer agreement was excellent (ICC > 0.90 for both modalities). Conclusion: Ultrasound demonstrates high correlation and acceptable agreement with CT in assessing splenic volume, supporting its utility as a reliable, non-invasive alternative in routine clinical settings, especially where CT is contraindicated or unavailable.